Phenomenology of Parenting while Schooling among Filipino College Student Mothers in the Province - Sicam, Eunica B; Umawid, Marianne D; Colot, Jhonnabhelle D; Dagdag, Januard D; Handrianto, Ciptro (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2021)
This phenomenological study sought to explore the lived experiences of student mothers enrolled in a Philippine higher education institution situated in the province. Participants were determined using a purposive sampling technique with the following criteria: currently enrolled in the higher education institution; has at least a child; 20 years old or above. FB Messenger was used in interviewing and gathering the research data. From the thematic data analysis, four major themes were revealed: (1) challenges faced by student mothers; (2) advantages of being a student mother; (3) managing time in dual roles; and (4) support by others. The student mothers face challenges in performing their dual role such as bullying, time management, and financial problem. The student mothers, however, get source of inspiration, respect, school excuses, and important lessons in life. Their parenting experience gives them a strong personality and an inspiration to continue their education pursuits. Though managing time is really hard for them, they are able to surpass it through time management and parental help. Support systems such as their teachers, classmates, parents, friends, and relatives also play a significant role in their lives. This study provides understanding on how to make tertiary education more accessible and transformational most especially to women who handle the dual roles as students and parents.